Enhanced modeling of photovoltaic modules through optimized estimation of series and shunt resistances from measured I-V curves - David Chepp, Ellen; Perin Gasparin, Fabiano; Krenzinger, Arno (Revista Principia, 2025)
The five-parameter single-diode model is widely employed to simulate the current-voltage (I-V) characteristics of photovoltaic (PV) modules. However, the estimation of series resistance (Rs) and shunt resistance (Rsh) from measured curves depends on the specific data ranges selected for linear regressions: in the short-circuit region for Rsh and in the open-circuit region for Rs. This study investigates the impact of the data range selection in the I-V curve on the analytical determination of Rs and Rsh. I-V curves measured under standard test conditions (STC) were used to calibrate the model, and its performance was assessed under varying irradiance and temperature levels. Differences in maximum power and RMSE of the modeled curves were analyzed. Selecting the I-V data range from zero current to 10% of the current at maximum power (IMP) for Rs, and from zero voltage to 50% of the voltage at maximum power (VMP) for Rsh, yielded the most accurate results, particularly under low-irradiance conditions (< 500 W/m2). Differences in modeled maximum power reached up to 12.9% when less appropriate data ranges were used. These findings contribute to a more robust modeling of PV modules under real-world operating conditions and may serve as a baseline for post-processing measured I-V curves of polycrystalline silicon PV modules to determine series and shunt resistances.